Treatment Options for Juvenile Idiopathic Arthritis (JIA) Associated Uveitis. (2nd January 2016) - Amin, Rowayda M.; Miserocchi, Elisabetta; Thorne, Jennifer E.; Hornbeak, Dana; Jabs, Douglas A.; Zierhut, Manfred
ABSTRACT: Purpose : To summarize the available published data regarding the treatment of JIA-associated chronic uveitis. Methods : Available peer-reviewed publications regarding the treatments of JIA-associated uveitis were read by multiple authors (RMA, EM, JET, and DH) and the data from these reports were synthesized for this review. Results : Juvenile idiopathic arthritis (JIA)-associated chronic uveitis is a significant cause of ocular morbidity and visual impairment in children, often resulting in more frequent complications and worse visual outcomes than other types of pediatric uveitis. Since not all patients respond to the first medication introduced, it is useful to have a wide range of available treatment modalities to address recalcitrant disease. Treatment options for JIA-associated uveitis have increased substantially over the past decade, particularly with the availability of newer biological agents in addition to established medication classes such as anti-inflammatories (including topical and systemic corticosteroids) and antimetabolites. Conclusions : Although data are increasing regarding biologic agents, definitive randomized prospective clinical trials would be helpful to determine their optimal dose, frequency, treatment duration, and long-term safety in children.